Roads to agency : Effects of Enhancing Women’s Participation in Rural Roads Projects on Women’s Agency - World Bank Group (World Bank, Washington, DC, 2015)
Infrastructure projects, and more specifically, roads construction, and maintenance are one of the core operations of the World Bank. However, despite the increase of gender mainstreaming efforts in transport projects little is known about the effects of these interventions on women’s agency defined as the ability to make effective choices and transform these choices into desired outcomes’. This study aims to bridge this knowledge gap. The study looks at the effects of women’s participation in roads construction and maintenance and rural economy promotion activities on women’s agency, which has recently become a focus of study at the World Bank. Through individual interviews and focus groups the study assesses the effects of women-targeted interventions in three rural transport projects in Argentina, Nicaragua, and Peru. By focusing on agency, the study sheds light on effects of gender mainstreaming interventions that have more lasting effects on gender equality given the catalytic value of agency on other gender outcomes such as economic opportunities and endowments. The report is structured as follows: section one gives introduction. Second section describes the gender dimensions and agency-enhancing approaches in transport projects and the gender approaches in project implementation in the selected case studies. The third section provides a summary of the methodology of the study. The fourth section describes the key findings of the qualitative research. The fifth section presents the lessons learned to inform future rural transport interventions. The sixth section provides concluding remarks.